Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1108/17538391011054354
|View full text |Cite
|
Sign up to set email alerts
|

Are Saudi banks productive and efficient?

Abstract: PurposeThe purpose of this paper is to estimate the data envelopment analysis (DEA) efficiency scores and Malmquist productivity indices of banks in Saudi Arabia, an economy that is heavily dependant on the hydrocarbon sector.Design/methodology/approachThe paper adopts the intermediation approach of banking services where financial institutions like banks are perceived to be manufacturing units, employing inputs such as interest and non‐interest expenses to produce outputs such as net interest and non‐interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Granger causality test showed that there was only a one-way relationship between ROE and ROA. Akhtar (2010) attempted to calculate the degrees of technical efficiency and productivity growth for banks in the KSA using the Data Envelopment Analysis (DEA) methodology. The results indicated that inefficiency stems from technical inefficiency in particular.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Granger causality test showed that there was only a one-way relationship between ROE and ROA. Akhtar (2010) attempted to calculate the degrees of technical efficiency and productivity growth for banks in the KSA using the Data Envelopment Analysis (DEA) methodology. The results indicated that inefficiency stems from technical inefficiency in particular.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, despite the importance of the banking industry in Saudi Arabia, fewer studies have attempted to analyse the efficiency of its banking industry. Some of the few studies are Akhtar (2010), Assaf et al (2011), andFaraj et al (2006), who investigated the technical efficiency of Saudi banks before major structural changes were adopted due to the WTO membership (joined in 2005), the implementation of Basel II and III accords (introduced in 2004 and 2010), and the Saudi stock market's crisis (occurred in 2006). Furthermore, the Saudi Vision 2030, which was announced in 2016, aims to increase the size and efficiency of the Saudi financial sector.…”
Section: Introductionmentioning
confidence: 99%